1983
DOI: 10.1002/chin.198308143
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Reaktion von Cyclopentadien-trans-dioxid mit Aminen.

Abstract: Die aus dem Monoepoxid (I) erhaltene Titelverbindung (II) wird mit den Aminen (III) umgesetzt.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1991
1991
1991
1991

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Independent reaction of the two epoxide moieties was usually found. In contrast to this, Kozlov et al [9] reported some years ago that trans-1,2:3,4-diepoxyc:yclopentane (1) reacted with secondary amines to give a product 4 with a central epoxy group which obviously arose from a 1,4-addition (Scheme 2). Besides 4, the expected 1,2-addition products 2 and 3 were observed.…”
mentioning
confidence: 91%
“…Independent reaction of the two epoxide moieties was usually found. In contrast to this, Kozlov et al [9] reported some years ago that trans-1,2:3,4-diepoxyc:yclopentane (1) reacted with secondary amines to give a product 4 with a central epoxy group which obviously arose from a 1,4-addition (Scheme 2). Besides 4, the expected 1,2-addition products 2 and 3 were observed.…”
mentioning
confidence: 91%